REGIONAL ECONOMY AND FOREIGN INVESTMENT AS CATALYSTS FOR GROWTH - Gafurov , Sherzod Abduvakhob ugli; Sabirova , L.Sh. (Educational Research in Universal Sciences, 2023)
This article delves into the intricate relationship between regional economies and foreign investment, elucidating the catalytic role played by the latter in fostering robust growth. The exploration begins with an overview of foreign investment, emphasizing the dynamic nature of capital flows across borders, with a focus on Foreign Direct Investment (FDI). The discussion unfolds to highlight how foreign investment serves as a powerful stimulant for economic growth in regions, injecting capital that fuels infrastructure development, technological advancements, and human capital improvement.